Understanding The Impact Of Covid-19 Pandemic On Corporate Branding Strategies - Mia Christy Patricia; Cahyatih Kumandang (Politeknik Kampar, 2024)
This research aims to investigate the effects of the COVID-19 pandemic on corporate branding strategies. Employing a phenomenological approach, the study delves into the lived experiences of corporate stakeholders amidst the pandemic. The sampling technique involves purposive sampling of corporate representatives and marketing professionals renowned for their expertise in branding strategies. Data collection is conducted through in-depth interviews, allowing for a rich understanding of participants' perceptions and experiences. Thematic analysis is employed to identify patterns, trends, and emergent themes from the interview data. Preliminary findings indicate shifts in branding strategies towards digital platforms, heightened emphasis on brand authenticity, and a reevaluation of brand messaging in response to the evolving socio-economic landscape influenced by the pandemic.